Major Histocompatibility Complex (MHC) Class I Processing of the NY-ESO-1 Antigen Is Regulated by Rpn10 and Rpn13 Proteins and Immunoproteasomes following Non-lysine Ubiquitination - Golnik, Richard; Lehmann, Andrea; Kloetzel, Peter-Michael; Ebstein, Frédéric (The Journal of biological chemistry, 2016)
The supply of MHC class I-restricted peptides is primarily ensured by the degradation of intracellular proteins via the ubiquitin-proteasome system. Depending on the target and the enzymes involved, ubiquitination is a process that may dramatically vary in terms of linkages, length, and attachment sites. Here we identified the unique lysine residue at position 124 of the NY-ESO-1 cancer/testis antigen as the acceptor site for the formation of canonical Lys-48-linkages. Interestingly, a lysine-less form of NY-ESO-1 was as efficient as its wild-type counterpart in supplying the HLA-A*0201-restricted NY-ESO-1157–165 antigenic peptide. In fact, we show that the regulation of NY-ESO-1 processing by the ubiquitin receptors Rpn10 and Rpn13 as a well as by the standard and immunoproteasome is governed by non-canonical ubiquitination on non-lysine sites. In summary, our data underscore the significance of atypical ubiquitination in the modulation of MHC class I antigen processing.